Atomic‐Scale Designing of Zeolite Based Catalysts by Atomic Layer Deposition. Issue 13 (25th May 2021) - Xu, Dan; Yin, Junqing; Gao, Ya; Zhu, Di; Wang, Shuyuan
Abstract: Zeolite‐supported catalysts have been widely used in the field of heterogeneous catalysis. Atomic‐scale governing the metal or acid sites on zeolites still encounters great challenge in controllable synthesis and developing of novel catalysts. Atomic layer deposition (ALD), owing to its unique character of self‐limiting surface reactions, becomes one of the most promising and controllable strategies to tailor the metallic deposition sites in atomic scale precisely. In this review, we present a comprehensive summary and viewpoint of recent research in designing and engineering the structural of zeolite‐based catalysts via ALD method. A prior focus is laid on the deposition of metals on the zeolites with emphasis on the isolated states of metals, followed by introducing the selected metals into channels of zeolites associates with identifying the location of metals in and/or out of the channels. Subsequently, detailed analysis of tailoring the acid sites of different zeolites is provided. Assisted synthesis of zeolite and the regioselective deposition of metal on special sites to modify the structures of zeolites are also critically discussed. We further summarize the challenges of ALD with respect to engineering the active sites in heterogeneous zeolite‐based catalysts and provide the perspectives on the development in this field. Abstract : Designing zeolite catalysts : This review provides a comprehensive summary and perspective concerning the strategies to engineer the metal/acid sites and channel structures on zeolite by atomic layer deposition (ALD).